2023
DOI: 10.47162/rjme.63.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced choroidal melanoma with favorable molecular prognosis – case report

Abstract: Uveal malignant melanoma is a rare malignant tumor comprising less than 5% of melanoma cases. It is nevertheless the intraocular tumor with the highest incidence in adults, that arises from the melanocytes in the uveal tract. The authors present the case of a patient with locally advanced choroidal melanoma: from presentation to diagnosis, treatment, and prognosis. A 63-year-old female patient presented in the Ambulatory of the Emergency County Hospital, Craiova, Romania, on the February 1, 2021, accusing visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As MM metastases can occur in a high percentage of cases and hold a very unfortunate prognosis for MM patients, the time until the diagnostic of the first metastasis is a very important indicator of evolution [ 3 , 27 , 28 , 29 ]. Correlation of the MMPs expression with this indicator reveals some aspects with high significance in the patients’ management.…”
Section: Discussionmentioning
confidence: 99%
“…As MM metastases can occur in a high percentage of cases and hold a very unfortunate prognosis for MM patients, the time until the diagnostic of the first metastasis is a very important indicator of evolution [ 3 , 27 , 28 , 29 ]. Correlation of the MMPs expression with this indicator reveals some aspects with high significance in the patients’ management.…”
Section: Discussionmentioning
confidence: 99%
“…Basal squamous cell carcinoma (so-called metatypical carcinoma) is a tumour that includes mixed regions with typical basaloid differentiation and regions approaching squamous cell carcinoma. [18,43,44] An aggressive, infiltrative type of BCC showed a high expression of an apoptotic gene Bcl-2 and moderate levels of proliferation associated markers -proliferating cell nuclear antigen. [44].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[18,43,44] An aggressive, infiltrative type of BCC showed a high expression of an apoptotic gene Bcl-2 and moderate levels of proliferation associated markers -proliferating cell nuclear antigen. [44]. It was found that telomere length was shortened and gene expression correlated with cell proliferation (Bcl-2, Ki-67) was increased in BCC [45].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It roots from the melanin-producing melanocytes originating from neural crest that migrated to uvea. [1] In melanoma originating from the eye and adnexa, (82.5%) of cases were primary uveal melanoma. Around 85-90% of uveal melanoma cases arise from the choroid, 5-8% from the ciliary body, and 3-5% from the iris.…”
mentioning
confidence: 99%